2003
DOI: 10.1097/00004770-200302000-00002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Cytotoxicity of Two Root Canal Sealers on Macrophage Activity

Abstract: Although some studies have been concerned with the cytotoxicity of endodontic sealers and their components, few have approached the effects of endodontic sealers on macrophage viability and activity. In this study the effect of two zinc oxide-eugenol-based sealers, freshly prepared or after setting for 24 h, was determined on macrophage activity in vitro. Sealers were placed inside a glass capillary tube and added to mouse-elicited macrophage cultures. Sealers did not affect macrophage viability; however, adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 15 publications
6
42
0
4
Order By: Relevance
“…According to Oliveira Mendes et al (21), although zinc oxide-eugenol sealers did not interfere with the macrophages' viability, their adherence and phagocytosis are affected in contact with this sealer, which could explain giant cells mobilization to eliminate the material. Moreover, after 60 days, Endofill showed significant higher scores for macrophages compared to the control group and presented a tendency for higher scores of neutrophils and abscess.…”
Section: Discussionmentioning
confidence: 97%
“…According to Oliveira Mendes et al (21), although zinc oxide-eugenol sealers did not interfere with the macrophages' viability, their adherence and phagocytosis are affected in contact with this sealer, which could explain giant cells mobilization to eliminate the material. Moreover, after 60 days, Endofill showed significant higher scores for macrophages compared to the control group and presented a tendency for higher scores of neutrophils and abscess.…”
Section: Discussionmentioning
confidence: 97%
“…The preservation of cytoplasmic extensions is important, because these extensions form a three-dimensional network within hard tissue and materials [16,31,[36][37][38]. The factors that affect cellular response to calcium phosphates include surface topography (roughness), composition and particle size.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that lower concentrations of eugenol can easily reach an effective cytotoxic level on USO2 cells during longterm exposure. Eugenol is capable of inhibiting the function of macrophages and thus affects the inflammation of periapical tissues (11).…”
Section: Scientific Journal Of the Faculty Of Medicine In Niš 2015;32mentioning
confidence: 99%